Factors related to the dynamics of dengue in Guayaquil based on historical trends - Real - Cotto, Jhony Joe (2017)
Introduction: Guayaquil population has an endemic – epidemic presence of dengue and there are few studies on the historical trend of the factors that influence its behavior. Objective: To establish the historical trend of factors relate to the dynamics of dengue in the city of Guayaquil during the period 2008 - 2013. Design. Non-experimental study, longitudinal trend. Setting: City of Guayaquil, Ecuador. Material: Cases of dengue. Methods: Information on cases of Dengue, temperature, humidity and wind, Breteau index and circulating viruses were obtained. Main outcome measures: Historical trend of the factors that influence the dynamics of dengue. Results: The trend with the most cases occurred in weeks 10-24 in 2010 and 2012, with scattering points compared to the trend line. Environmental variables showed findings of moisture above 70% with high and low winds that can cause conditions that  may increase the transmission of the disease. The study also showed that there are epidemiological periods when the transmission decreases that may be related to lower temperatures, relative humidity and presence of wind. The 4 serotypes of dengue were present, with simultaneous movement of DEN1, DEN2 serotypes, and DEN4 serotypes for the past 3 years. Conclusions: The historical trend of dengue throughout the year has periods and years of variability. Environmental factors like temperature, humidity, winds and Breteau index accounted for more cases in the first 2 periods of each year. The polynomial trend was 63.3% which can be considered reliable on the increase in cases for the projection for 2017. It is important to continue the studies of the historical behavior of dengue with an integrated approach.